The Big Data Gap: Asymmetric Information in the Ophthalmology Residency Match Process and the Argument for Transparent Residency Data - Le Breton, Stephen Adam; Desai, Shilpa (Journal of Academic Ophthalmology, 2023)
Background The ophthalmology match is an important step for graduating medical students that defines their future career. Residency programs demonstrate significant variability due to differences in size, location, research output, subspecialty exposure, surgical case load, and alumni fellowship/practice placement. Despite the importance of informed decision-making, applicants often find limited, inconsistent information about potential programs.Purpose The purpose of this study was to characterize and identify gaps in the information available to residents in the 2022 to 2023 Match.Methods The SFMatch Web site was reviewed to identify programs included as well as characteristics cited on each program's webpage. Program webpages were used to evaluate availability and consistency of data on site surgical caseload, fellowship slots, and teaching staff.Results Of the 121 programs included on SFMatch, 23 (19%) provided no data on August 15, 2022 (15 days prior to application submission deadline) and 9 (7%) lacked program data on October 15, 2022. Though most programs provided mean cataract volume, data on volume of other procedures for graduating residents was highly variable and occasionally misleading. Programs did not provide information on several academic and social considerations that may influence match ranking choice.Conclusion Applicants often must read “between the lines” to identify residency program strengths and weaknesses. Data crucial to informing the application process remain sparse, unavailable, or spread across resources. Limited data increases applicant dependence on word-of-mouth knowledge to inform decision-making. This might reduce diversity by limiting successful applicants to those with existing connections within the field.
Keywords: residency match; SFMatch; transparency